Influence of false beliefs and empathy on white lies among children with mild intellectual disabilities: focusing on trait and state perspectives - Zhen, Zeng; Liming, Meng (Frontiers in Psychology, 2024)
Children with mild intellectual disabilities often exhibit poor social skills owing to intellectual impairments. This makes it essential to enhance their communication abilities. This study provides a novel contribution by systematically investigating the effects of false beliefs and empathy on white lie behavior among children with mild intellectual disabilities, considering both state and trait dimensions. Experiment 1 examined the impact of trait-level false beliefs and trait-level empathy on trait-level white lies. The results demonstrated that trait-level false beliefs and trait-level empathy both significantly promoted white lie behavior. Experiment 2 explored the influence of state-level false beliefs and state-level empathy on state-level white lies and found similar positive effects. By integrating both trait and state perspectives, this research fills a gap in the literature on white lie behavior in children with mild intellectual disabilities and uncovers the mechanisms through which false beliefs and empathy operate in different contexts. These findings offer comprehensive educational and intervention strategies to improve social adaptation in children with mild intellectual disabilities.